KEMASAN DAN PEMASARAN PRODUK COCTAIL ‘PINKUER’ MENGGUNAKAN BAHAN DASAR SAGUER - Lagarense, Bet El; Pesik, Mex U.; Pamikiran, Silvia R. (UPT Penelitian Sekolah Tinggi Ilmu Pariwisata Manado, 2024)
Marketing or marketing is inseparable from the term Marketing Mix which includes (Place, Product, Price, Primotion) or 4Ps. Pinkuer is one of the products that has a selling value for the welfare of local people, especially saguer farmers in Minahasa. With Pinkuer, local people can further improve the quality of Saguer which will affect turnover or income and can cultivate sugar palm plants which have long been a typical plant of the people of North Sulawesi or better known as (Seho Trees). Attractive and quality packaging can add value to the product and increase market competitiveness. With a new product to raise the name of an area then how to promote it. Like wise with the way of presentation or packaging that is as creative as possible in order to increase sales levels, to be more competitive with other beverage products.